Penerapan Good Governance Pada Pengelolaan Dana Desa Di Desa Matagara Kecamatan Tigaraksa Kabupaten Tangerang - Febrianti, Yulia; Asmawi, M. Rosul; Santoso, Seno (Universitas Serang Raya, 2024)
The aim of this research is to determine the application of good governance in managing village funds in Matagara Village, Tigaraksa District, Tangerang Regency. This study used qualitative research methods. Data collection uses observation, interviews and documentation methods. The results of this research show that the implementation of good governance in the management of village funds in Matagara Village has gone well based on the principle of accountability, makes an accountability report in the form of LPJ and uses the siskeudes application as a form of accountability for the village head. On the principle of effectiveness and efficiency, various projects or activities are in accordance with the needs of village communities. However, in principle, transparency is not yet optimal because the transparency provided by the government is only through billboards or banners in villages and information regarding budgets and activities in villages is not communicated through other information media such as village websites. In principle, village community participation is always involved by the government in every village meeting to convey input regarding their respective areas. In principle, village government rules and laws apply to activities or projects from the planning stage to accountability in accordance with applicable rules and laws.